Analisa Opini Publik tentang Mutu Pelayanan E-KTP di UPTD Pelayanan Adminduk Kecamatan Baki Sukoharjo - Setyo Purwanto; Diana Sukorina (Jurnal Media Administrasi, 2025)
This research was conducted to determine the quality of e-identity card (e-KTP) making services provided by UPTD Administrative Services Subdistrict Government Baki Regency, which is measured through several indicators of service quality, namely: direct evidence, reliability, responsiveness, assurance, empathy, and communication. In addition, this research was also conducted to determine the constraining factors of the quality of e-KTP services which can be seen from the facilities and infrastructure, service procedures, and the ability of employees. This study uses a qualitative descriptive approach with data collection obtained from observations and interviews. The results of this study indicate that the quality of service for making e-KTP in UPTD Baki Subdistrict has been maximized which can be seen from the guarantee of definite completion, adequate facilities and infrastructure, good attention and response from employees, high employee responsiveness and being able to provide reliable information. Researchers suggest that the UPTD Baki Subdistrict further improve the performance of its employees by conducting training for employees, adding facilities and infrastructure and also clarifying information about service procedures.